Impact of ball-milling time on the physical properties, bioactive compounds, and structural characteristics of onion peel powder. (August 2020) - Jiang, Guihun; Ramachandraiah, Karna; Wu, Zhaogen; Li, Shanji; Eun, Jong-Bang
Abstract: The effect of ball-milling time on the physical properties, bioactive compounds, and structural characteristics of onion ( Allium cepa L.) peel powder were studied. Extending the ball-milling time increased the water solubility index, bulk and tapped densities, Carr index, and brightness of onion peel powder, but decreased its water holding capacity and redness. Moreover, ball-milling for 18 h showed increased total phenolic content and antioxidant activity but decreased when ball-milling time was extended to 24 h. Total flavonoid contents and protocatechuic acid remained unaffected. No change in quercetin content was observed up to 12 h. However, quercetin content significantly decreased when ball-milled for 24 h. Scanning electron microscopy images showed the shape and surface morphology of onion peel powder of different sizes. A longer ball-milling time affected the functional groups and crystalline structure of the onion peel powder. Therefore, a specific ball-milling time (18 h) and speed set (300 rpm) can produce a fine onion peel powder with improved physical properties and antioxidant activity, thereby adding value to food products and promoting health benefits.